Acceptability of fish cake prepared from Aristichthys nobilis (A. nobilis) and Nemipterus sp. - Yu, S.Y.; Lee, S.Y. (1989)
The aim of this study was to evaluate the sensory characteristics of fish cake prepared from a.nobilis and from nemipterus sp. nemipterus sp. is normally used to prepare fish cake in Malaysia. This is due to its white flesh and it gives good texture to the final product. Formulations incorporating the flesh from these two species were tested using both fresh meat and those frozen at -18 C for 16 days. In addition to tapioca flour, which is normally used, wheat and corn flours were also tried out as posibble substitutes. Results showed that products made from 100% A. nobilis (sample A) were very well received by taste panelists and were rated higher than commercial products. The leaching process improved colour, flavour and binding properties of the fish cake. Leaching also removed some of the fat which might otherwise interfere with gel formation. Fish cake made with 80% A. nobilis : 20% Nemipterus (sample B) and 60% A. nobilis : 40% Nemipterus (sample C) were also acceptable by taste penelists. The scores for fish cake made from frozen fish showed that the 100% A. nobilis sample was significantly superior in texture,flavour and overall acceptability compared to samples B and C. However,there were no significant differences between fish cakes prepared from fresh fish and those from frozen fish. Penelists were unable to detect significant differences with the usage of tapioca, wheat and corn flours used in the fish cake formulation, although samples with tapioca flour generally received the highest scores.